Exploring the energy landscape of bacterial chromosome segregation - Sumitabha Brahmachari; Antonio B. Oliveira; Matheus F. Mello; Vinícius G. Contessoto; José N. Onuchic (Proceedings of the National Academy of Sciences, 2026)
Faithful chromosome segregation during bacterial replication requires global reorganization of the nucleoid, where Structural Maintenance of Chromosomes (SMC) complexes play a crucial role. Here, we develop an energy landscape framework that integrates data-driven pairwise interactions with coarse-grained polymer physics to infer the 3D architectural ensembles of Escherichia coli and Bacillus subtilis chromosomes throughout replication. We show that SMC-mediated long-range lengthwise compaction reshapes the nucleoid to induce a robust mid-replication transition in which the terminus relocates toward the nucleoid center and duplicated origins segregate toward opposite cell halves. SMC-deficient mutants lack this transition and instead exhibit emergent nematic-like alignment of sister chromosomes that impedes segregation. A distinctive intersister Hi-C signature accompanies the emergence of the nematic alignment. By systematically tuning nonspecific intersister adhesion, we reveal that SMC activity expands the physical regime permitting faithful segregation. This buffering protects segregation against adhesive forces intrinsic to the crowded bacterial nucleoid. Our framework provides mechanistic insight into SMC-dependent coreplication segregation across bacterial species, yielding experimentally testable predictions for imaging and sister-chromosome-resolved Hi-C.